Constraints Experienced by Women Entrepreneurs in Managing Poultry and Handicraft Enterprises - A, Vennila Mary; G, Tamilselvi (Journal of Extension Education, 2025)
A study was conducted with 150 women entrepreneurs managing poultry and handicraft enterprises in Tirupattur District of Tamil Nadu, India to identify the constraints they faced. The main production constraints experienced by the women entrepreneurs in poultry were high mortality rates, high costs of good-quality feed, and other inputs. The major marketing constraints they encountered were rumours about hormone injection and other alleged health hazards associated with consuming poultry meat and products. Similarly, the major constraints experienced by them in handicraft production were shortages of raw materials, lack of skilloriented training, and inadequate finance. The major marketing constraints the women entrepreneurs faced were lack of transportation and price fluctuations. These insights can help address the challenges faced by women entrepreneurs in these sectors.